2010
DOI: 10.1074/jbc.m110.121863
|View full text |Cite
|
Sign up to set email alerts
|

An Autoregulatory Loop between Nrf2 and Cul3-Rbx1 Controls Their Cellular Abundance

Abstract: The cellular defense system protects against oxidative stress caused by a vast range of xenobiotics, inflammation, and ionizing radiation (1-3). Disruption of these protective systems causes the accumulation of reactive oxygen species (ROS) 2 and electrophiles that can contribute to diseases such as cancer, cardiovascular complications, acute and chronic inflammation, and neurodegenerative diseases (4). Therefore, it is obvious that cells must constantly labor to control levels of ROS, preventing them from acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Therefore, it appears that cells contain mechanisms that autoregulate cellular abundance of Nrf2 (27,28). Based on the reported studies, it is suggested that the Nrf2 up-regulation of ARE-mediated gene expression is an early response to antioxidants (1,2).…”
mentioning
confidence: 99%
“…Therefore, it appears that cells contain mechanisms that autoregulate cellular abundance of Nrf2 (27,28). Based on the reported studies, it is suggested that the Nrf2 up-regulation of ARE-mediated gene expression is an early response to antioxidants (1,2).…”
mentioning
confidence: 99%
“…It is induced on day 3 in HP and reaches a maximum of 8.2-folds on day 6. NRF2 is is phosphorylated by PERK, and it later auto-regulates its own mRNA expression (Kaspar and Jaiswal 2010;Stępkowski and Kruszewski 2011). NRF2 also induces the expression of anti-oxidant responsive genes (Chen and Kunsch 2004).…”
Section: Dynamics Of Perk Signaling Branch Of Upr Pathwaymentioning
confidence: 99%
“…Immunoblot analyses were performed as previously described ( 23 ). For whole extract, 2 mg equivalents of heart tissue homogenates were subjected to SDS-PAGE, transferred to a nitrocellulose membrane, and probed with specifi c antibodies against Plin2-5 and Nrf2 ( 23,27 ). GAPDH (1:1000) (Cell Signaling, Beverly, MA) and ␤ -actin (1:5000) (Sigma, St. Louis, MO) were used as the housekeeping genes.…”
Section: Western Blot Analysismentioning
confidence: 99%